Research Article - Khan, Javeria; Qureshi, Muqadas; Rasheed, Arif; Yousuf Farooq, Syed Muhammad (British journal of radiology, 2025)
To compare transabdominal and transvaginal ultrasound for the assessment of cervical length in the third trimester of pregnancy. In this cross-sectional analytical study, a total of 500 pregnant women were screened, out of which 223 women, aged 18 to 45 years, with a gestational age of 26-30 weeks in the third trimester, were enrolled. Prior to participation, all subjects provided written informed consent and were made aware of the potential risks and benefits associated with the procedure. Clinical and demographic data, including risk factors and medical history, were collected using a pre-designed data collection form. Gestational age was determined based on the last menstrual period. TAS and TVS measurements of cervical length were made on 229 pregnancies of 26-40 weeks gestation. Out of 223 patients, there were 102 females had lower abdominal pain there were 100 females had bleeding and 126 females had cephalic position and breech 97. at 223 women were initially enrolled in the study. Paired TAS and TVS measurements were obtained in 123 (51.3%) women. The mean TVS CL was 35.2 ± 6.8 mm, and the mean TAS CL was 34.7 ± 6.5 mm. Significant differences were identified between the mean CL measurements of the two techniques (P < 0.05). both TAS and TVS are valuable tools for cervical length assessment, TVS should be considered the gold standard for more accurate and reliable measurements, especially in clinical settings where precise monitoring of cervical length is necessary. By providing a novel comparison between transvaginal and transabdominal ultrasonography for the assessment of cervical length in the third trimester, this study advances our understanding of how to optimize measuring methods for the reduction of preterm birth risks.